Perioperative Management of Type-3c Gaucher's Disease for Kyphoscoliosis Correction and Spinal Cord Detethering - Ahmed, Tasneem F.; Mariappan, Ramamani; Ramadas, Sreekumar M.; D'Souza, Wilson P.; Raju, Krishnaprabhu (Journal of Neuroanaesthesiology and Critical Care, 2025)
Gaucher's disease (GD) is an inherited lysosomal storage disorder caused by mutations in the acid β-glucosidase (GBA) gene, leading to abnormal function of the enzyme glucocerebrosidase, which results in the accumulation of glucocerebrosides in various organs, causing multiorgan dysfunction. GD has three phenotypes, of which type-3 is the cardiovascular type with many anesthetic implications. A 20-year-old woman, genetically proven type-3 GD, was diagnosed with thoracolumbar kyphoscoliosis with fatty filum and planned for deformity correction and fatty filum excision. She had mitral and aortic stenoses, hydrocephalus, corneal opacity, a difficult airway, and chronic pain. Management of a difficult airway, hemodynamic management in double stenotic lesions, and perioperative pain management were considered as some of the challenges. The intraoperative course was complicated by massive blood loss and pneumothorax, which were managed appropriately. Perioperative pain was managed using a multimodal analgesic technique. Thorough preoperative evaluation, meticulous planning, and execution with adequate backup plans and appropriate pain management helped with faster recovery.
Keywords: aortic stenosis; type-3c Gaucher's disease; kyphoscoliosis correction; mitral stenosis; massive blood loss and transfusion